Effect of Establishing a Separate Outpatient Pharmacy Counter on Reducing Waiting Time in Mayapada Hospital - Irham, Hanifan; Basabih, Masyitoh (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2025)
Pharmacy waiting time is one of the quality indicators that affects patient satisfaction in hospitals. One of the various efforts to reduce drug waiting times is adding outpatient pharmacies. This study aims to see whether the addition of pharmacies based on guarantors can reduce drug waiting times for outpatients. This is an observational study with a cross-sectional design. The sample included 11,703 patients who received prescriptions at Mayapada Hospital Bogor outpatient with insurance and private coverage. Data were collected over four months, two months before and two months after the separation of pharmacies. Waiting time data were obtained from the hospital’s Health Information System (HIS). Univariate analysis showed that most patients visited the hospital during the noon shift (51.1%). Patients with private coverage dominated at 50.8% and non-compounding drugs dominated at 68.7%. There was a time difference of 1 minute and 22 seconds before, and 1 minute and 17 seconds after, the addition of the pharmacy for patients in the private coverage category with insurance. The Mann-Whitney test results get a p-value =